Pengaruh Soundscape pada Sense of Place di Perpustakaan Daerah Disarpus Bandung - Widiarini, Nabila Anindya; Pasaribu, Yannes Martinus; Vidyarini, Etika (Serat Rupa: Journal of Design, 2023)
Sound is one of the important elements in forming the impression and experience of space. In the context of the library as a social space, the sounds that come from the various activities of space users then enrich the library's acoustic environment. This study aims to evaluate the effect of subjective perception of audial soundscape on the formation of a sense of place in public libraries using a descriptive quantitative qualitative method through observation, recording, and distributing questionnaires using an accidental sampling method. The Public Collection Room and Co-working Space at the Bandung City Archive and Library Services (Disarpus Bandung) were chosen as research objects considering the character of the space and the context of the library. The results of data analysis show that sound objects in the natural sound category are preferred by respondents and have a positive correlation with sense of place in both spaces of Public Collection Room and Lobby. Some sound objects from the category of human activity such as conversations and footsteps have a positive correlation, while chair squeaks and children's voices have a negative correlation. There are differences in preferences for several sound objects that follow the function of the room, such as the sound of keyboard/mouse typing is preferred in the Lobby, while the sound of turning book pages is preferred in the Public Collection Room. Layout and openings also affect exposure to traffic noise, which is significantly negatively correlated in the Lobby, but not in the General Collection Room. The character of the soundscape in the Bandung Disarpus Library as a social space creates positive associations between users and places through comfort, conductivity, and social interaction. These factors are created through the soundscape as well as forming a sense of place following the function of space.